Time-domain aeroelastic model for compound helicopter propeller-wing configuration - Wang, Zi; Anobile, Alessandro; Popov, Atanas A. (2017)
A simplified numerical model for time-domain aeroelastic analysis of a wing structure in a propeller-wing configuration is described in the paper. A linear beam model with deformable elastic axis under torsional deformation and out-of-plane bending is considered to simulate a wing structure with tip mounted propeller, relying on efficient, analytical formulations. The complete aeroelastic system of equations is solved using Galerkin’s approach, and numerically integrated by the Newmark-beta method. The computational tool developed is able to predict the wing aeroelastic transient behaviour and the wing-propeller interaction effects in the time domain. The purpose of such a tool is to provide accurate enough predictions of the system aeroelastic response to be included in structural optimisation and control synthesis procedures. A complete analysis on the solver used and an aeroelastic analysis of a Eurocopter X3-like compound helicopter wing/propeller configuration are demonstrated.